Closure duration as a cue to stop consonant voicing - a developmental study in 3-6 year old kannada speaking children - Sathya Krishnamurthy (Journal of All India Institute of Speech and Hearing, 1970)
One of the basic unresolved issues in the study of speech and language is the complex relationship between production and perception. Applied tochildren, it is important to understand the modification process that the child undergoes to document the status of phoneme perception during the yearsthe child is acquiring the phonology in production. Studies have suggested that a developmental or masturational differences in the closure durationphoneme boundary width in children (Simon 1974, Zlatin & Koenigsknecht 1975) are present.